Quaint Korea - Miln, Louise Jordan (Moffett Korea collection., 1895)
A few words about Hamel -- Some curious Korean customs -- Söul from the city wall -- Korea's king -- Korean women -- Korean women (continued) -- Korean architecture -- How the Chinese, the Japanese, and the Koreans amuse themselves -- A glance at Korean art -- Korea's irreligion -- Korea's history in a nutshell -- The scourges of China -- Japan's ingratitude -- Glossary.